Migration of non-Brownian particles localized inside sheared droplets. (November 2022) - Van Ammel, Helene; Ferreira, Joana; Kruitwagen, Axel; Fransen, Senne; Moldenaers, Paula; Kuhn, Simon; Cardinaels, Ruth
Highlights: Particles inside sheared droplets migrate along the vorticity direction. The migration direction depends on the viscosity ratio. The migration kinetics depends on Ca, interfacial tension and particle concentration. VOF simulations provide velocity and shear rate distribution in a particle-free droplet. Shear-induced migration plays a major role. Abstract: The migration of non-Brownian particles inside a droplet subjected to shear flow is investigated. The viscosity ratio, particle concentration, particle to droplet size ratio and capillary number are systematically varied. It was observed that particles migrate in the vorticity direction either towards or away from the equatorial plane. The main factor determining the migration direction is the viscosity ratio. The particle concentration and applied capillary number have no influence on the equilibrium distribution and only affect the time necessary to reach this distribution. In order to identify the flow profile, both velocity and shear rate magnitudes to which the particles inside the droplet are subjected, are numerically simulated using the Volume-of-Fluid method in a particle-free droplet/matrix system. The numerical predictions of the flow are used to evaluate the presence of possible driving mechanisms for cross-streamline particle motion, such as particle inertia and shear rate gradients. Depending on the conditions, the simulations reveal significant differences in the streamline profiles and shear rate gradients within the droplet. The observed steady state particle distributions can partially be explained by shear-induced migration towards zones of low shear rates and/or low streamline curvature. However, in complex flows, such as inside a deformed droplet, different migration mechanisms can occur simultaneously. Hence, confinement inside the droplet and potential secondary flows may also play a role. Graphical abstract: Image, graphical abstract